A new hydrophobic deep eutectic solvent composed of menthol and tris(2-ethylhexyl) phosphate for solvent bar microextraction of parabens from biological fluids - Nabil N. AL-Hashimi; Husam Abed Alfattah; Khaleel I. Assaf; Asma A. Fakhoury; Saja H. Hamed; Amjad H. El-Sheikh; Khairi M. Fahelelbom (Emerging Contaminants, 2024)
Parabens are antimicrobial preservatives with extensive applications in cosmetics, toiletries, pharmaceuticals, and food. Considering the legitimate concerns relating to their potential to disrupt multiple endocrine functions, it becomes imperative to prioritize the development of innovative bioanalytical techniques for effectively monitoring their presence in biological samples. In this study, an efficient solvent bar microextraction (SBME) was established, utilizing new hydrophobic deep eutectic solvents (DEs) to determine methylparaben and propylparaben in urine and plasma samples. The DEs comprising menthol and tris(2-ethylhexyl) phosphate (M-TEHP) at various molar ratios were synthesized for the first time to enhance the extraction capacity and promote the eco-friendliness of the DE used as an extraction solvent. Fourier-transform infrared (FT-IR) and proton nuclear magnetic resonance (1H NMR) spectroscopies were employed to confirm and investigate the properties of the successful synthesis (M-TEHP) DE at a molar ratio of 1:1. The synthesized DE exhibits low microbial toxicity and can be considered an eco-friendly solvent for extraction. Furthermore, quantum-chemical calculations were utilized to predict synthesized DE's structure and interaction energy with selected parabens. The influential operational factors of DE-SBME on the extraction efficiency (EE%) of both parabens were evaluated using response surface methodology based on central composite design, and a total of 30 extraction tests were conducted to determine the optimal conditions. The optimized DE-SBME, in combination with HPLC-DAD, exhibited low detection limits (0.54–0.91 μg L−1), excellent linearity (R2 ≥ 0.9993), precise results (RSDs ≤7.6 %), satisfactory recoveries (92–97 %) and negligible matrix effects. Hence, it had remarkable effectiveness and applicability in determining selected parabens in real urine and plasma samples.